2012
DOI: 10.1021/jz3018489
|View full text |Cite
|
Sign up to set email alerts
|

Proton Tunneling in Heterodimers of Carboxylic Acids: A Rotational Study of the Benzoic Acid–Formic Acid Bimolecule

Abstract: Tunneling effects have been measured in the pulsed jet Fourier transform microwave spectra of two isotopologues of the benzoic acid-formic acid bimolecule. The tunneling splittings are originated by the concerted proton transfer of the two carboxylic hydrogens. From the values of these splittings for the OH-OH and OD-OD species, it has been possible to model/size the barrier to the concerted double proton transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…Since the publication of results for the formic acid homodimer measurements in the infrared by Havenith et al, 1 there have been studies made on heterodimers in the microwave region and one study on a homodimer. A permanent dipole moment allows the study by rotational spectroscopy and the following systems have been reported: propiolic acid-formic acid, [2][3][4] acetic acid-formic acid, 5 formic acid-fluoroacetic acid, 6 formic acid-trifluoroacetic acid, and acetic acid-trifluoroacetic acid, 7 formic acid-benzoic acid, 8 and more recently the dimers of acrylic acid with fluoroacetic acid. 9 The analysis of the homodimer of acrylic acid 10 demonstrated proton tunneling amongst identical molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of results for the formic acid homodimer measurements in the infrared by Havenith et al, 1 there have been studies made on heterodimers in the microwave region and one study on a homodimer. A permanent dipole moment allows the study by rotational spectroscopy and the following systems have been reported: propiolic acid-formic acid, [2][3][4] acetic acid-formic acid, 5 formic acid-fluoroacetic acid, 6 formic acid-trifluoroacetic acid, and acetic acid-trifluoroacetic acid, 7 formic acid-benzoic acid, 8 and more recently the dimers of acrylic acid with fluoroacetic acid. 9 The analysis of the homodimer of acrylic acid 10 demonstrated proton tunneling amongst identical molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of results for the formic acid homodimer measurements in the infrared by Havenith et al, 1 there have been studies made on heterodimers in the microwave region and one study on a homodimer. A permanent dipole moment allows the study by rotational spectroscopy and the following systems have been reported: propiolic acid-formic acid, [2][3][4] acetic acid-formic acid, 5 formic acid-fluoroacetic acid, 6 formic acid-trifluoroacetic acid, and acetic acid-trifluoroacetic acid, 7 formic acid-benzoic acid, 8 and more recently the dimers of acrylic acid with fluoroacetic acid. 9 The analysis of the homodimer of acrylic acid 10 demonstrated proton tunneling amongst identical molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution. Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The formic acid dimer is the prototype system for this kind of investigation, but the lack of dipole moment inhibits rotational investigation. [4] In some cases, the barrier to the double proton transfer has been calculated from the splittings measured in several isotopologues. [14] Tunneling splittings in homo-dimers have been measured by rotationally resolved laser-induced fluorescence in the ground and first electronic-excited states of the benzoic acid dimer, [15] and recently by pure rotational spectroscopy in the homo-dimer of acrylic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation